Closing the gap potential contribution of social assistance for achieving sustainable development goals. - Handayani, Sri Wening (Metro Manila, Philippines Asian Development Bank, 2017)
This brief discusses the fiscal requirements to meet the social protection related targets of SDGs, particularly for social assistance programs in ADBs 16 developing member countries in Asia.
Keywords: Economic assistance; Sustainable development; Electronic books